Perencanaan Obat dengan Metode Abc di Apotek J Kecamatan Praya Lombok Tengah Tahun 2022 - Djuniarthi Aswinabawa (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
A drugstore is a pharmaceutical service facility that is used as a place for the implementation of drugstore practice by pharmacists. To maintain the availability of drugs, it is necessary to plan and procure good drugs which have a very important role to determine the stock of drugs that are in accordance with the needs of health services with guaranteed quality and can be obtained when needed. To see the success of drug planning, it is necessary to evaluate using the ABC method. This research is quantitative pre-experimental. The analytical method used is descriptive analytic method with ABC using quantitative data that has been available at Apotek J so this research is a retrospective study. The results showed that there were 150 drugs in group A of drugs with a percentage of 13.62% of the total types of drugs. The percentage of drug use is 70.90% with the value of drug use Rp. 119,409,000, drugs that are included in group B drugs are 269 kinds of drugs with a percentage of 24.43% of the total types of drugs. The percentage of drug use is 20.06% with a drug use value of Rp. 66,061,980. Drugs that are included in drug group C are 682 kinds of drugs with a percentage of 61.94% of the total types of drugs. The percentage of drug use is 9.04% with the value of drug use Rp 52,131,750.